Beyond Diversity: Focusing on and Enhancing Inclusion in the Society for Epidemiologic Research. Issue 10 (30th June 2020) - Moore, Kristin J; Xiong, Serena; Bhattacharya, Manami; Bustamante, Gabriela; Calvert, Collin
Abstract: Increasing diversity and inclusion among organizational membership has become a focus for many professional societies, including the Society for Epidemiologic Research (SER). In this issue of the Journal, DeVilbiss et al. ( Am J Epidemiol . 2020:189(10):998–1010) assessed dimensions of diversity and inclusion within SER to provide baseline data for future evaluations of Society initiatives. In our response, we note that diversity in SER appears strong but there is lag with regard to inclusion. We also highlight some of the major weaknesses of this study that hinder efforts to accurately evaluate inclusion within SER. There is a need to more concretely define inclusion and think broadly about how measures of inclusion should be operationalized in future surveys. Additional limitations of the study include its limited generalizability to the wider SER membership and the lack of questions about barriers to inclusion in SER activities. We conclude with recommendations for SER and other professional societies based on prior literature evaluating successful diversity and inclusion efforts. We also propose a conceptual model to assist with operationalizing and directing future analyses of inclusion measures. It is essential that SER move beyond efforts around diversity to focus on measuring and enhancing inclusion.